Temperature and composition dependence of viscosity, refractive index and thermodynamics of viscous flow for benzonitrile + methyl/ethyl/butyl methacrylate binary systems: Experimental and theoretical study - Anil Kumar Nain; Preeti Droliya (Chemical Thermodynamics and Thermal Analysis)
The viscosities, η and refractive indices, nD of pure benzonitrile, methyl methacrylate, ethyl methacrylate, n‑butyl methacrylate and of their binary mixtures with benzonitrile as common component, covering the entire composition range were measured at temperatures (293.15, 298.15, 303.15, 308.15, 313.15 and 318.15) K and atmospheric pressure. The experimental data have been correlated using the Jouyban-Acree model to represents the composition and temperature dependence of these physicochemical properties. Using the experimental data, the deviations in viscosity, deviations in refractive index and deviations in molar refraction have been calculated. These excess properties were correlated by the Redlich-Kister equation. The variations of these deviation parameters with composition and temperature have been discussed terms of prevailing intermolecular interactions in these mixtures and the magnitude of interactions follow the order: MMA > EMA > BMA. Additionally, the thermodynamic parameters, Arrhenius activation energy and Gibbs free energy, enthalpy and entropy of activation of viscous flow have also been calculated and analyzed to describe the thermodynamics of viscous behaviour of these systems. Further, the η and nD of the binary mixtures were calculated theoretically using various empirical/semi-empirical viscosity relations and refractive index mixing rules, respectively, and the results were compared with the experimental data.